Prevalence of impacted teeth among a sample of Yemeni population and their association with sex and age. - Amen Abdulkarem Hagar; Jameel Mohammed Helmi; Khaled Ahmed Al- Jawfi; Abulwahab Al- dilami; Mohammed Ali Al -Wesabi (Universidad de Concepción., 2019)
Aim: the aim of the study was to assess the prevalence of impacted teeth and its association with sex and age among a sample of the Yemeni population. Materials and Methods: A cross sectional study design was employed. The study included 999 radiographical records of patients who had panoramic X- rays previously done. All radiographs were assessed for the number and type of impacted teeth, pathology-associated impaction, sex, age and location (mandible and/or maxilla). The collected data was analyzed using SPSS®version21 software. Results: The study sample comprised digital panoramic radiographs of Yemeni patients aged 17 to 54 years (mean 26.6 years). The present study found 542 patients (54.3%) presented with at least one impacted tooth. The 17 to 25 years age group of the study sample had the highest prevalence of tooth impaction (28.6%). Only 10 (1.0%) case presented pathologies associated with the impacted teeth. There was a significant difference in the number of male 203 (20.3%) and female 339 (33.9%) patients with impacted teeth (p=0.031). Impacted teeth occurred slightly more often in the mandible (42.8%) compared to the maxilla (42.4%). Conclusion: The prevalence of impacted teeth among a sample of Yemeni population was high. Third molars and canines were the most common impacted teeth. The prevalence of impacted teeth in females was higher than in males and it was higher in the mandible than in the maxilla, with the younger patients with a higher prevalence of impaction.